"We Are Not Taking a Backseat": Health Social Workers' Perspectives on COVID-19 Response and Recovery. Issue 4 (16th September 2022) - Ross, Abigail M; Schneider, Samantha; Boskey, Elizabeth
Abstract: The COVID-19 pandemic has wrought widespread devastation across the United States, exacerbating existing health inequities rooted in the social determinants of health. Social work is the key workforce tasked with providing social care in healthcare settings. In September 2019, the National Academies of Science, Engineering, and Medicine released a landmark Consensus Study Report, Integrating Social Care into the Delivery of Health Care: Moving Upstream to Improve the Nation's Health . The report describes a framework for addressing key care needs that articulates five "As for action" (5As)—awareness, alignment, assistance, adjustment, and advocacy—that are critical to social care. Drawing from a series of focus groups conducted with 55 social workers employed in a large urban pediatric quaternary hospital, this study qualitatively examines the utility of this framework in characterizing social care activities during the pandemic response and recovery efforts. Findings suggest that the 5As framework is both applicable to pandemic social work practice and an accurate encapsulation of the core elements of hospital social work practice, even if social workers themselves may not necessarily be aware of that conceptualization. Future implications for social work practice in arenas of awareness, adjustment, assistance, alignment, and advocacy are also discussed.